ANALYSIS AND DESIGN OF EMPLOYEE PAYROLL ACCOUNTING INFORMATION SYSTEM AT PUBLIC ACCOUNTING FIRM OF TASNIM, FARDIMAN, SAPUAN, NUZULIANA, RAMDAN & PARTNERS - Aminudin, Fajri; Saripudin, Saripudin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to find out and at the same time analyze how the payroll system is currently being implemented at Public Accountant Firm Tasnim, Fardiman, Sapuan, Nuzuliana, Ramdan & Partners, whether the payroll system has been running effectively and propose a payroll accounting information system design at Public Accountant Firm Tasnim, Fardiman, Sapuan, Nuzuliana, Ramdan & Partners. The data used in this study is primary data obtained directly from Public Accountant Firm Tasnim, Fardiman, Sapuan, Nuzuliana, Ramdan & Partners and is a descriptive qualitative research, namely a case study using qualitative data obtained from internal companies. The data analysis technique used is system analysis, proceed to the proposed flowchart stage, proposed DFD, proposed ERD to payroll system design using Microsoft Access and Visual Basic 6.0. Based on the results of this study, the payroll system at Public Accountant Firm Tasnim, Fardiman, Sapuan, Nuzuliana, Ramdan & Partners still has problems in the payroll system, namely the procedure for payroll documents is still manual or still using handwriting and the calculations are still using the excel program whose input must use the formula complicated so that time is not efficient. Keywords: analysis and design, accounting information system, and employee payroll